0
$\begingroup$

If $w^3=1$

Solve $(1-w)(1-w^2)(1-w^4)(1-w^5)$

I am not sure how to go about this question, I attempted expand the equation and simplify it using the basic roots of unity theorems, but it was . I am asking if anyone has a simple way of solving equations of these sort.

Thank you.

$\endgroup$
  • $\begingroup$ Use the following $1+\omega+\omega^2=0$ and $\omega^3=1$. For example using the second property, we can write $\omega^5=\omega^2$ and so on. $\endgroup$ – Anurag A Nov 12 '18 at 4:41
1
$\begingroup$

I presume $w\ne 1$. Then $1+w+w^2=0$. Also $w^4=w$ and $w^5=w^2$. Your product is $$[(1-w)(1-w^2)]^2=(2-w-w^2)^2=3^2=9.$$

More generally, let $\zeta$ be a primitive $n$-th root of unity. That is $\zeta^n=1$ and $\zeta^d\ne1$ for $0<d<n$. Then $$X^n-1=(X-1)(X-\zeta)(X-\zeta^2)\cdots(X-\zeta^{n-1}).$$ Dividing by $X-1$ and letting $X\to1$ gives $$n=(1-\zeta)(1-\zeta^2)\cdots(1-\zeta^{n-1}).$$ Your formula is the square of this with $n=3$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.